Obesity and Insulin Resistance: Clinical Relevance Analysis of Multiple Metabolic Indicators in Insulin Resistance in Patients With Type 2 Diabetes - Feifei Li; Qiaofang Ke; Gaoyan Dai (Discovery Medicine, 2026)
Background: Type 2 diabetes mellitus (T2DM) is one of the most common chronic metabolic diseases worldwide, and insulin resistance is the core pathophysiological basis for its development. This study aims to explore the relationship between various metabolic-related indicators and insulin resistance in patients with T2DM, and to analyze the correlation between obesity indicators, glucose and lipid metabolism indicators, and serum uric acid with insulin resistance, providing a reference for clinical identification of insulin resistance.Methods: This was a single-center retrospective study, consecutively enrolling 263 patients with type 2 diabetes who received treatment at our center between August 2022 and August 2025. Patients were divided into a non-insulin-resistant group (n = 211) and an insulin-resistant group (n = 52) based on the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). Baseline clinical data and laboratory parameters were collected, including body mass index, waist-to-hip ratio, fasting blood glucose, 2-hour postprandial blood glucose, lipid profile, glycated hemoglobin, fasting C-peptide, and serum uric acid. The triglyceride-glucose (TyG) index was also calculated. Logistic regression analysis was performed to screen for metabolic indicators associated with insulin resistance, and receiver operating characteristic (ROC) curve analysis was then conducted to evaluate the discriminative ability of these indicators for insulin resistance.Results: Patients in the insulin resistance group had significantly higher levels of body mass index (BMI), waist-to-hip ratio (WHR), triglycerides, fasting blood glucose, TyG index, fasting C-peptide, glycated hemoglobin (HbA1c), systolic blood pressure, diastolic blood pressure, and serum uric acid than the non-insulin resistance group (all p < 0.05), and a higher proportion of patients with hypertension (65.38% vs. 46.45%, p = 0.014). Multivariate logistic regression analysis showed that WHR, TyG index, fasting C-peptide, and serum uric acid were independently associated with insulin resistance. The area under the curve (AUC) for assessing insulin resistance using the combined indicators was 0.81 (95% CI: 0.74–0.88), with a sensitivity of 79.0% and a specificity of 71.0%.Conclusion: In patients with type 2 diabetes, WHR and serum uric acid levels are significantly correlated with insulin resistance status. These indicators reflect various metabolic characteristics from different perspectives, including obesity, glucose and lipid metabolism, and pancreatic β-cell function, and may provide preliminary insights into the metabolic abnormalities associated with insulin resistance in patients with type 2 diabetes.